Kaposi’s Sarcoma-Associated Herpesvirus, but Not Epstein-Barr Virus, Co-infection Associates With Coronavirus Disease 2019 Severity and Outcome in South African Patients - Blumenthal, Melissa J.; Lambarey, Humaira; Chetram, Abeen; Riou, Catherine; Wilkinson, Robert J.; Schäfer, Georgia (Frontiers in Microbiology, 2022)
In South Africa, the COVID-19 pandemic occurs against the backdrop of high Human Immunodeficiency Virus (HIV-1), tuberculosis (TB) and non-communicable disease burdens as well as prevalent herpesviruses infections such as Epstein-Barr virus (EBV) and Kaposi’s sarcoma-associated herpesvirus (KSHV). As part of an observational study of adults admitted to Groote Schuur Hospital, Cape Town, South Africa, during the period June – August 2020 and assessed for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, we measured KSHV serology and KSHV and EBV viral load (VL) in peripheral blood in relation to Coronavirus disease 2019 (COVID-19) severity and outcome. A total of 104 patients with PCR-confirmed SARS-CoV-2 infection were included. 61% were men and 39% women with a median age of 53 years (range 21 – 86). 29.8% (95% CI: 21.7 – 39.1%) of the cohort was HIV-1 positive and 41.1% (95% CI: 31.6 – 51.1%) were KSHV seropositive. EBV VL was detectable in 84.4% (95% CI: 76.1 – 84.4%) of the cohort while KSHV DNA was detected in 20.6% (95% CI: 13.6 – 29.2%), with dual EBV/KSHV infection in 17.7% (95% CI: 11.1 – 26.2%). On enrolment, 48 (46.2% (95% CI: 36.8 – 55.7%)) COVID-19 patients were classified as severe on the WHO ordinal scale reflecting oxygen therapy and supportive care requirements; 30 of these patients (28.8% (95% CI: 20.8 – 38.0%) died. In COVID-19 patients, detectable KSHV VL was associated with death after adjusting for age, sex, HIV-1 status and detectable EBV VL (p=0.036, adjusted OR=3.17 [95% CI: 1.08 – 9.32]). Furthermore, in HIV-1 negative COVID-19 patients, there was a trend indicating that KSHV VL was related to COVID-19 disease severity (p=0.054, unstandardized co-efficient 0.86 [95% CI: -0.015 – 1.74]) in addition to death (p=0.008, adjusted OR=7.34 [95% CI: 1.69 – 31.49]). While the design of our study cannot distinguish if disease synergy exists between COVID-19 and KSHV nor if either viral infection is fueling the other, these data point to a potential contribution of KSHV infection to COVID-19 outcome, or SARS-CoV-2 infection to KSHV reactivation, particularly in the South African context of high disease burden, that warrants further investigation.